The Non-athletic Ideal - Meintani, Anastasia (Jahrbuch des Deutschen Archäologischen Instituts, 2024)
[The article has been retracted.]Small-scale figurines having a misshapen appearance were exceptionally en vogue in the Hellenistic and Roman times. Scholars have attributed a wide gamut of functions to them. The underlying common denominator of all the propounded theories is that the purpose of these images, no matter what they depict, was tο lampoon and degrade the dregs of society and/or the physically deformed. The same is held to be true for those representing athletes. This paper argues, based on visual comparanda and literary sources, that such statuettes actually poked fun at the ideal of physical and athletic prowess.